Estrategias de aprendizaje basadas en el uso de juegos didácticos para la enseñanza de las tablas de multiplicar en estudiantes de quinto año de EGB, de la Unidad Educativa San Miguel, del cantón San Miguel de la provincia Bolívar, durante el año lectivo 2024- 2025. - Agualongo Agualongo, María Inés (2025)
This research highlights the importance of educational games and the various subtopics addressed in the theoretical framework, which will be very helpful in identifying the problems and determining which educational games can aid in improving the learning of multiplication tables among fifth-grade students at San Miguel Educational Unit during the 2024–2025 school year. Educational games are fundamental in this field as they offer meaningful learning through play. These methods motivate children to learn by combining fun with education. Furthermore, they encourage independence and collaborative learning, highlighting the achievements of all students. A survey instrument consisting of ten questions was used and applied to fifth-grade EGB students. This tool made it possible to observe the students' progress in learning multiplication tables. The results showed that a large percentage of students demonstrated a good level of learning in this area. However, it was identified that further improvement could be achieved through the implementation of educational games, which would contribute to a stronger academic foundation for students.